Mumps Caused by an Inadequately Attenuated Measles, Mumps and Rubella Vaccine - WJ Bakker; RG Mathias (Canadian Journal of Infectious Diseases)
PROBLEM: Reports of mumps following measles, mumps and rubella (MMR) immunization.